Dynamic economic growth: A new method of approach - Villalbos Céspedes, Daniel (2020)
This paper looks at Harrod’s fundamental assumptions and equations in ‘An essay in dynamic theory’ as the foundation for suggesting a better understanding of his postulates on economic growth. The analysis we present attempts to measure the effects of resource composition on the field of economic growth by determining its elasticity and the coefficient of acceleration. By addressing new critical assumptions, key formulas, and methods of approach, some crucial findings provide a strong theoretical model with which to examine dynamic economic growth. Furthermore, this paper offers a brief review of Solow’s and Swan’s critiques of Harrod’s essay. This analysis could inspire further advances in the study of economic growth at the academic level and even in terms of government macroeconomic policies and business decisions.